Visceral Fat Area, Not Subcutaneous Fat Area, is Associated with Cardiac Hemodynamics in Type 2 Diabetes - Qiu Y (Dove Medical Press, 2020)
Yue Qiu, Xia Deng, Yujing Sha, Xunan Wu, Panpan Zhang, Ke Chen, Zhicong Zhao, Weiping Wei, Ling Yang, Guoyue Yuan, Li Zhao, Dong Wang Department of Endocrinology, Affiliated Hospital of Jiangsu University, Zhenjiang, Jiangsu 212001, People’s Republic of ChinaCorrespondence: Dong Wang; Li ZhaoDepartment of Endocrinology, Affiliated Hospital of Jiangsu University, 438 Jiefang Road, Zhenjiang, Jiangsu 212001, People’s Republic of ChinaTel +86-13605282460; +86-15800578209Email zjdongdonghao@aliyun.com; zhaoli863@163.comBackground: This study was conducted in patients with type 2 diabetes mellitus (T2DM) to assess the association between visceral fat area (VFA) and cardiac hemodynamics.Methods: A total of 568 patients with type 2 diabetes (mean age 54± 12 years; 40.8% of women) were enrolled. Visceral fat area (VFA, m2) and subcutaneous fat area (SFA, m2) were evaluated by a bioelectrical impedance analyzer. Cardiac hemodynamics were measured by echocardiography, and other clinical and laboratory variables were also assessed and recorded. Patients were divided into those with VFA ≤ 100 (n=369) and those with VFA > 100 (n=199).Results: VFA, SFA, LVMI (left ventricular mass index), left atrial diameter, left ventricular diastolic diameter (LvDd), interventricular septal thickness (IVST), left ventricular systolic diameter (LvSd), and posterior wall thickness (PWT) levels in high-V groups were significantly higher than those in low-V groups. Correlation analysis showed that VFA was positively correlated with LVMI (r=0.120, p=0.004), LVM (r=0.249, p< 0.0001), left atrial diameter (r=0.375, p< 0.0001), aortic root diameter (r=0.243, p< 0.0001), left ventricular systolic diameter (LvSd) (r=0.211, p< 0.0001) and negatively correlated with LVEF (r=− 0.107, p=0.011). In multivariate linear regression analysis, VFA was the strongest independent determinant of LVMI (β=0.04, p=0.016), LVEF (β=− 0.01, p=0.023), and left atrial diameter (β=0.035, p< 0.0001), Internal diameter of the aortic root (β=0.014, p< 0.0001) and LvSd (β=0.017, p< 0.0001). In addition, the VFA also better predicted cardiovascular disease risk with AUC of 0.609 (95% CI:0.563– 0.656), compared with SFA, waist–hip ratio (WHR), in a statistically significant manner.Conclusion: We found a significant correlation between VFA (but not SFA) and cardiac hemodynamic parameters. The VFA has advantages as a predictor of visceral obesity and is significantly associated with the development of cardiovascular risk factors (CVD) in T2DM patients.Keywords: cardiac hemodynamics, left ventricular mass index, type 2 diabetes mellitus, visceral fat area